Specific judo exercises for developing relative repetitive strength - Kustro, N.; Budinscak, M. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
The study has shown that with the help of belt martial arts, as a very simple and cheap tools, you can do very high quality training to develop strength in the open or in areas of modest material conditions.